2019
DOI: 10.1039/c8cp07685e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydrogen vacancies in KDP and ADP crystals: a combination of density functional theory calculations and experiment

Abstract: KDP and ADP crystals were grown by the rapid growth method, and the origin of the extra optical absorption in both crystals has been explored by theoretical method. The calculation results well explain the experimental phenomenon, and confirm the existence of hydrogen vacancies in both crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…The defect models with Cr atoms replacing K, P, and H atoms and interstitial positions are constructed. The defect formation energies of defects with charge state q dependent on the Femi level position were defined as: [30][31][32][33][34][35][36][37][38][39][40][41][42][43]…”
Section: Computational Details and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The defect models with Cr atoms replacing K, P, and H atoms and interstitial positions are constructed. The defect formation energies of defects with charge state q dependent on the Femi level position were defined as: [30][31][32][33][34][35][36][37][38][39][40][41][42][43]…”
Section: Computational Details and Resultsmentioning
confidence: 99%
“…The defect models with Cr atoms replacing K, P, and H atoms and interstitial positions are constructed. The defect formation energies of defects with charge state q dependent on the Femi level position were defined as: 30–43 where E total ( X q ) and E total (pristine) are the total energies of supercells with and without defects, respectively. n i is the specific number of atoms removed or added to the supercell.…”
Section: Resultsmentioning
confidence: 99%
“…The defect formation energies of defects with the charge state q dependent on the Fermi level position were defined as: 15 where E f ( X q ), E tot ( X q ) and E tot (pristine) are the defect formation energy of the system, total energy of the defective system, and total energy of the pristine system, respectively; n i , μ i , and q are the number of atoms removed or added from the supercells, chemical potential of the defective element, and number of charges carried by the defect, respectively; E f , E v and Δ V are the positions of the Fermi energy level, valence band maximum (VBM) and difference between the average electrostatic potential of the defect system and pristine KDP, respectively. The chemical potential of H was calculated halving the energy of H 2 , and the value was −3.62 eV.…”
Section: Computational Detailsmentioning
confidence: 99%
“…23 The electronic structure and optical properties of the Fe-doped crystal were calculated by Liu et al 26 The absorption spectra indicated that the Fe-doped crystal has optical absorption in the long-wave region. Sui et al 27 used this calculation method to further investigate the effect of the charge state and internal microscopic stress of point defects on the stability and optical absorption of the crystal structure. The influence of the existence of different point defects on the optical properties of the crystal was explored, but the direct relationship between point defects and laser damage of crystals has not been revealed yet.…”
Section: Introductionmentioning
confidence: 99%